ANALISIS PERBANDINGAN PENERIMAAN DANA ZAKAT SEBELUM DAN SESUDAH PENERAPAN PAYROLL SYSTEM - Gita Nurul Fitri Damanik; Juliana Nasution (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2023)
The potential for zakat in Indonesia is very high but in reality the collection of zakat is still low. With the existence of various services from Baznas, for example zakat via the payroll system, it should be able to increase the receipt of zakat funds in Indonesia. This research was conducted at the National Amil Zakat Agency, Pematang Siantar City. The research period used was 2 years before (2017-2018) and 4 years after (2019-2022). This study aims to compare the receipt of zakat funds before and after the implementation of the payroll system. Comparative analysis of various aspects of receiving zakat funds based on the objectives of the payroll system, which includes increasing the amount of zakat received, simplifying time, and optimizing professional zakat by increasing the number of muzzaki. In this comparative quantitative study, the Independent Sample T-Test analysis was used to determine whether the average value of zakat funds received before and after the payroll system was the same or not significantly different. When compared to the conventional assumption test, the data normality test performs better than the graph test. The conclusion of the hypothesis testing reveals the ratio of professional zakat. Sig. Value of 0.523 (two-tailed) greater than 0.05, the independent sample t test can be used to determine whether H0 is accepted or rejected. As a result, it is possible to draw the conclusion that there is no real and significant difference in the average results of receiving zakat funds prior to and following the implementation of the payroll system.